What happens to patients who leave without being seen in an emergency department? - Cardozo-Ocampo, Alejandro; Grajales, Yeimi Natalia (CES Medicina, 2019)
Patients who leave without being seen from the emergencys services represent a risk, because some of them may have diseases that can eventually lead to major adverse events.